2013
DOI: 10.1111/aji.12138
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-Alpha, Interleukin-6, and Interleukin-10 Levels are Altered in Preeclampsia: A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis with accompanying summary of non-parametric data shows elevated maternal circulating TNF-α, IL-6, and IL-10 levels in preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
135
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(159 citation statements)
references
References 98 publications
18
135
0
2
Order By: Relevance
“…When we treated HUVECs with esomeprazole ( Figure 4A), there was a significant increase in phosphorylated eNOS (p-eNOS, the active form). Cotreatment of tumor necrosis factor-α (TNF-α; a proinflammatory cytokine that circulates in excess in preeclampsia 28 and likely contributor to endothelial dysfunction 29 ) with esomeprazole and rabeprazole at different doses all induced a nonsignificant increase in p-eNOS protein ( Figure S6A and S6B). These data suggest the PPIs upregulate p-eNOS expression.…”
Section: Proton Pump Inhibitors May Be Promoting Vasodilation By Modumentioning
confidence: 99%
“…When we treated HUVECs with esomeprazole ( Figure 4A), there was a significant increase in phosphorylated eNOS (p-eNOS, the active form). Cotreatment of tumor necrosis factor-α (TNF-α; a proinflammatory cytokine that circulates in excess in preeclampsia 28 and likely contributor to endothelial dysfunction 29 ) with esomeprazole and rabeprazole at different doses all induced a nonsignificant increase in p-eNOS protein ( Figure S6A and S6B). These data suggest the PPIs upregulate p-eNOS expression.…”
Section: Proton Pump Inhibitors May Be Promoting Vasodilation By Modumentioning
confidence: 99%
“…In addition, Haider and Knöfler [7] reported that TNF-α induces the production of MMP-9 from primary trophoblasts, which may help to maintain pregnancy. Accordingly, alterations of these cytokine levels may be associated with abnormal pregnancy conditions, such as recurrent abortions and preeclampsia [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, the mother develops Treg specificity for fetal antigens and, similarly, the fetus develops Tregs with specificity for non‐inherited maternal antigens 1, 2, 3. During preeclampsia, there is significant evidence demonstrating markers of maternal immune activation as part of the disease 7. In contrast, investigations of the fetal immune response during preeclampsia are limited with no published studies regarding fetal Treg changes in preeclampsia.…”
Section: Introductionmentioning
confidence: 99%